2015
DOI: 10.1007/s13193-015-0446-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Contrast Enhanced Ultrasound Technique to Wire Localization of Sentinel Lymph Node in Patients with Early Breast Cancer

Abstract: Axillary staging is one of the primary steps in management of Breast cancer patients. Current standard methods including blue dye and radicolloid have limitations and disadvantages. In this study, the feasibility of visualization of lymph node pathways and localization of SLN with the help of CEUS was assessed. 50 patients with early breast cancer diagnosis underwent CEUS and wire localization, methylenblue dye, and isotope scan methods for SLN detection. The pathology findings of the wired SLN were compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…Of 567 studies identified from the initial search, 35 cohort studies (4244 subjects) satisfied the inclusion and exclusion criteria, and were included in this meta‐analysis (Fig . , Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 567 studies identified from the initial search, 35 cohort studies (4244 subjects) satisfied the inclusion and exclusion criteria, and were included in this meta‐analysis (Fig . , Table ).…”
Section: Resultsmentioning
confidence: 99%
“…, Table ). Among the studies included, 22 15,16,20–23,26,27,30–32,34,35,38–41,43–45,47,49 reported on the performance of ICG, eight on SPIO and five on CEUS. The mean age of included subjects was 57 years.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, lymphosonography also identifies at least one SLN in 89% to 97% of patients, which is not different from the traditional techniques. 30,[32][33][34] An average of 1.2 (74/62) SLNs per MCT was identified using CEUS, whereas an average of 1.6 (88/54) SLNs per MCT was identified with lymphoscintigraphy/ intraoperative methylene blue, when compiling the cases from two studies. 15,16 It is difficult to compare these figures, but it is possible that the dual-labelled technique truly identifies a higher number of LNs.…”
Section: Sln Sonographic Characteristicsmentioning
confidence: 99%
“…24 The potential of this technique was validated in canine models, [25][26][27][28] prior to application in human patients diagnosed with breast cancer and cutaneous melanoma. [29][30][31][32][33][34] The main advantages are the wide availability of CEUS, low cost, safety and rapid clearance of the contrast, 35 no requirement for general anaesthetic, quick contrast diffusion to the LNs in real-time, 27 the ability to view the fine details of the lymphatics and LNs, 36 and minimal spillover of the contrast to secondary nodes. 28,37 The main disadvantages are the need to select which lymphatic basins to scan, and inter-operator variability.…”
mentioning
confidence: 99%
“…Of the 16 selected studies, 9 used SonoVue as CEUS material [26][27][28][39][40][41][42][43][44], 6 used Sonazoid [23][24][25][45][46][47], and 1 used DEFINITY [48]. The administration sites and methods of contrast agents mainly include intradermal [23-28, 39-44, 47] and subcutaneous [45,46] injection around areola or peritumoral parenchyma injection approaching the axilla [48].…”
Section: The Localization Detection Rate Of Ceus For Slnmentioning
confidence: 99%